Penerapan data antropometri siswa dalam perancangan tempat berwhudu di SDIT ATH Thaariq – 2 Dumai - Fitra Fitra; Desyanti Desyanti; Mustazihim Suhaidi (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2020)
ABSTRACTSDIT ATH-THAARIQ 2 Muhammadiyah Dumai is one of the integrated Islamic elementary schools in the city of Dumai, has a vision of realizing a generation of Qur'ani, Islamic civilized, intelligent, achievers, towards a global-minded human being. SDIT ATH-THAARIQ 2 Muhammadiyah Dumai accustoms their students to perform prayers in congregation and duha prayers every day, practice Islamic etiquette such as eating and drinking courtesy, courtesy at the toilet, courtesy to old parents, procedures for taking wudhu correctly and memorization of Juz Amma. To take whudu still use the water closet (WC) that available in each class with a size of 2m x 1m and the school still provides 1 faucet so that when student take wudhu they have to queue. The initial observations of the position of the faucets in the WC were not appropriate with the anthropometry of the students of SDIT ATH-THAARIQ 2 Muhammadiyah Dumai. So we need a place of Wudhu that can meet the needs when taking wudhu by making a place of wudhu with the position of the tap in appropriate with the average anthropometric data of students of SDIT ATH-THAARIQ 2 Muhammadiyah Dumai. The results of wudhu place design with the application of anthropomteri data are the height of the faucet from the floor is 79.25 cm, the width of the distance between the faucets is 50 cm and the body distance to the faucet is 30.80 cm Keywords: Anthropometry, SDIT ATH-THAARIQ 2 Muhammadiyah Dumai, Wudhu ABSTRAKSDIT ATH-THAARIQ 2 Muhammadiyah Dumai merupakan salah satu sekolah dasar islam terpadu yang ada di Kota Dumai, memiliki visi mewujudkan generasi Qur’ani, beradab islami, cerdas, berprestasi, menuju insan berwawasan global. SDIT ATH-THAARIQ 2 Muhammadiyah Dumai membiasakan  siswa-siswinya untuk melaksanakan sholat berjama’ah dan sholat dhuha setiap hari, mengamalkan adab – adab islami seperti adab makan dan minum, adab ke WC, adab kepada oarang tua, tata cara mengambil wudhu yang benar  serta hafalan – hafalan Juz Amma. Untuk pengambilan whudu masih menggunakan water closet (WC) yang tersedia di setiap kelas dengan ukuran 2m x 1m dan sekolah masih menyediakan 1 kran sehingga pada saat pengambilan air wudhu siswa - siswi harus mengantri. Hasil pengamatan awal posisi kran yang ada di WC belum sesuai dengan antropometri siswa-siswi SDIT ATH-THAARIQ 2 Muhammadiyah Dumai. Maka diperlukan tempat wudhu yang bisa memenuhi kebutuhan saat pengambilan air wudhu tersebut dengan membuat tempat wudhu yang posisi krannya sesuai rata-rata data antropometri siswa - siswi SDIT ATH-THAARIQ 2 Muhammadiyah Dumai. Hasil perancangan tempat berwudhu dengan penerapan data antropomteri adalah tinggi kran dari lantai adalah 79,25 cm, lebar jarak antara kran adalah 50 cm dan jarak tubuh ke kran adalah 30,80 cm. Kata kunci: Antropometri, SDIT ATH-THAARIQ 2 Muhammadiyah Dumai, Wudhu.